Keabsahan Perjanjian Paylater (Bayar Nanti) Pada Aplikasi Gojek Menurut KUH Perdata - Tiara Iga Mandera; Suraji Suraji (Aliansi: Jurnal Hukum, Pendidikan dan Sosial Humaniora, 2024)
This study aims to determine the validity of the agreement between Gopay Later according to the Indonesian Civil Code. This research is a normative juridical legal study with a legislative approach. Based on this research, it is found that the electronic agreement of Gopay Later between consumers and PT. Multifinance Anak Bangsa (Gojek) can be considered valid according to Indonesian contract law and does not contradict the Indonesian Civil Code.